EFEKTIVITAS PENGGUNAAN FLIPBOOK DIGITAL DALAM MENINGKATKAN LITERASI SAINS PADA MATA PELAJARAN IPAS KELAS IV - Fitria Dwi Ines Shinta, Yolanda; Kukuh, Andriyas; Sulistyo, Sulistyo; Dwi Ferdiani, Rosita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effectiveness of using digital flipbooks in improving students' scientific literacy in fourth-grade science at SDN Gadang 4 Malang. This study used the Classroom Action Research (CAR) method, implemented in two cycles, including planning, implementation, observation, and reflection. The subjects were 28 fourth-grade B students, selected purposively due to their low scientific literacy skills. Data collection techniques included observation, pretests and posttests, documentation, and student response questionnaires. The results showed that the use of digital flipbooks was effective in improving students' scientific literacy. In Cycle I, the percentage increase in learning outcomes reached 49.34%, with a learning completion rate of 78.57%. In Cycle II, the improvement in learning outcomes increased to 82.67%, and students demonstrated more active learning participation. The paired sample t-test results showed a significance value of 0.000 (<0.05), indicating a significant difference between the pretest and posttest scores. Furthermore, students' responses to the use of digital flipbooks were very positive, as learning became more engaging, interactive, and easier to understand. Thus, digital flipbooks have been proven effective in improving students' scientific literacy in fourth-grade science lessons.